Ionómeros de vidrio : utilidad en odontopediatría (1994)
ABSTRACT: Characteristics of glass ionomers that make of them useful materials in pediatric dentistry are reviewed: cariostatic potential, bonding to dental tissues, dentin-pulp complex response, physical properties, and their clinical implications. Finally, this review presents suggestions for a correct technique when using glass ionomer products, because their sensitivity is still an important drawback.